PELUANG DAN TANTANGAN PENGEMBANGAN POTENSI DAERAH MELALUI KOMUNITAS ASEAN 2015 - Haqqi, Halifa (Transformasi, 2011)
Abstract Asean Community as regional community in southeast asia built by concern many country. That purpose to make southeast asia better than before. With 3 pilars, first politics and security, second economic and the third socio culture. The role number 37 years1999 especially local government Asean Community has opportunity to built relationship with other country, beside challenges for local government to face it. Keywords: Asean community, opportunity and challenges